What's different about bank holding companies? - Ralph Chami; Thomas F. Cosimano; Jun Ma; Céline Rochon (Journal of Risk and Financial Management, 2022)
We develop a dynamic model of a BHC that encompasses both a trading desk and a loan desk, and explore the role of risk attitude and overleveraging by the trading desk. We trace the impact of monetary policy and market innovations on bank behavior in the presence of Basel III type regulations. We show that the value of the BHC is enhanced by operating both desks. We explore alternative regulatory remedies to ongoing efforts to ring-fence the proprietary trading business, and show that regulations that target bank governance can mitigate possible rogue trading and the overleveraging problem.
Keywords: 650; financial markets; bank capital; bank holding company; banking; Basel III; financial stability; macro prudential; monetary policy; ring-fencing; term structure